The Development of Learning Instrument Using Problem Based Learning Model to Improve Critical Thinking of Junior High School Students - Yusrina Santri Nasution; Edi Syahputra; Mulyono Mulyono (BIRCU, 2020)
The study aims to: (1) determine the validity and effectiveness of learning instrumentswhich are developed, (2) determine the increase of critical thinking skills of student using learning instruments developed. This research is development research. The Development model used is 4-D model which consists of four stages: defining, designing, development and disseminate. The results of the defining phase are used to design a learning instrument, thenthis draft is validated and tested in the classto see its effectiveness. From this development, result obtained are: (1) The learning instrument developed is valid with an average validity total of lesson plan = 4.35, student books = 4.35, student worksheet = 4.36; (2) The learning instrumentis effective, that can be seen from both the individual and classical learning mastery are achieved, student activities within the specified tolerance limits and the student’s response toward learning instruments are in good categories; (3) the increasing average of critical thinking skills of students from first trial test to second trial test is 0.20 points.